Evaluasi Penerapan Manajemen Risiko pada Kegiatan Cleaning Tanki dengan Metode HIRARC di PT. DEF - Butar Butar, Putri Stephany; Rahmawati, Nur (Fakultas Teknik Universitas Tulang Bawang, 2025)
Human resources is very important role in carrying out activities in an organization or company. So companies need to strive for a safe working environment to maximize HR potential. One important aspect that must be considered in human resource management is the occupational safety and health system. Therefore, this research aims to evaluate how K3 management has been implemented by PT. DEF during the tank cleaning process using the HIRARC method. Tanks are an example of a confined space. which refers to an area that is quite large but has limited access in and out and is potentially dangerous because the atmosphere contains dangerous gases or air with the most extreme risk, namely that it can threaten worker safety. The results of this research are that in the 6 stages of the tank cleaning process there is a 46% moderate level risk, 31% high level risk, and 23% extreme level risk. After conducting a risk assessment analysis, it can be concluded that PT. DEF has been effective in implementing risk management in tank cleaning activities, this is proven by the company being able to reduce all risks in tank cleaning activities in an efficient manner. Keywords: Cleaning Tanki, Confined Space, Hazard, Risk Assessment